An analysis of the countervailing measures used to address the anti-competitive effects of Government subsidies in the African Continental Free Trade Area - Matsimbi, Rhulani Shaun (Rhodes University, Faculty of Law, Law)
Government subsidies are becoming more prevalent on the African continent. Subsidies allow the government to intervene in markets to incentivise more investment into nascent and struggling industries by improving the efficiency of firms in such industries. As such, subsidies form an essential part of some African countries' industrialisation policies. However, the use of subsidies faces a challenge because of the prohibition contained in the World Trade Organisation's (WTO) Agreement on Subsidies and Countervailing Measures (SCM Agreement). The SCM Agreement prohibits the granting of subsidies that are contingent on export performance or the use of domestic over imported content. While African countries have not faced challenges in the WTO for their use of these subsidies, this may change with the operation of the African Continental Free Trade (AfCFTA) Agreement. This is because the AfCFTA Agreement localises the WTO's rules on subsidisation. This study critically examines the provisions in the AfCFTA Guidelines on the Implementation of Trade Remedies that regulate the use of export subsidies and subsidies contingent on the use of domestic content. It discusses how the absolute prohibition of these subsidies in the AfCFTA Agreement is not the most effective way to regulate their anti-competitive effects in the African continent. Specifically, this study discusses the role that competition policy might play in ensuring that export subsidies and local content subsidies are regulated in a manner that suits Africa's context. Ultimately, this study concludes and recommends that the AfCFTA must develop unique rules to regulate subsidies in a way that caters to the needs of the continent.
Keywords: Subsidies -- Law and legislation -- Africa; Agreement on Subsidies and Countervailing Measures (1994 April 15); Trade regulation -- Africa; World Trade Organization; Antitrust law -- Africa; Restraint of trade -- Africa; African Continental Free Trade (AfCFTA) Agreement